Smack : heroin and the American city - Schneider, Eric C., 1951-2017 (Politics and culture in modern America., 2008)
Through interviews with former junkies and clinic workers and in-depth archival research, Schneider also chronicles the dramatically shifting demographic profile of heroin users. Originally popular among working-class whites in the 1920s, heroin became associated with jazz musicians and Beat writers in the 1940s. Musician Red Rodney called heroin the trademark of the bebop generation. "It was the thing that gave us membership in a unique club," he proclaimed. Smack takes readers through the typical haunts of heroin users - 52nd Street jazz clubs, Times Square cafeterias, Chicago's South Side street corners - to explain how young people were initiated into the drug culture." "Smack recounts the explosion of heroin use among middle-class young people in the 1960s and 1970s. It became the drug of choice among a wide swath of youth, from hippies in Haight-Ashbury and soldiers in Vietnam to punks on the Lower East Side. Panics over the drug led to the passage of increasingly severe legislation that entrapped heroin users in the criminal justice system without addressing the issues that led to its use in the first place. The book ends with a meditation on the evolution of the war on drugs and addresses why efforts to solve the drug problem must go beyond eliminating supply.